Experimental Study of the Thermal and Dynamic Behaviors of Polypropylene Fiber-Reinforced Concrete - Liu Lei; Lizhe Dong; Huaming An; Yuqing Fan; Ya Wang (Applied Sciences, 2021)
The wide use of high-performance concrete (HPC) makes it essential to study its dynamic and thermal behavior. In this study, polypropylene fiber-reinforced high-performance concrete was developed and a series of tests were carried out to obtain its mechanical and thermal properties. Since high-strength HPC has previously been studied intensively, only low-strength HPC—i.e., C30, C40, and C50—was studied in this research. The split Hopkinson pressure bar (SHPB) was employed to carry out the dynamic tests of the HPC under various loading rates and the principles of the SHPB were introduced in detail. Then, the polypropylene fiber-reinforced HPCs were heated to various high temperatures and measures were taken to keep the temperatures relatively constant. It was found that at temperatures lower than 100 °C, the specimen could still be kept in its entirety, although many fractures were produced in the HPC specimen under dynamic loading conditions. However, it was found that at temperatures higher than 200 °C, all the HPC samples were smashed into fragments. In addition, the HPC’s compressive strength was found to be significantly influenced by the temperature. At temperatures lower than 300 °C, the HPC’s compressive strength was found to increase with increases in temperature. At temperatures higher than 300 °C, the HPC’s compressive strength was found to decrease with increases in temperature.